Nano-LC-MS/MS for Quantification of Lyso-Gb3 and Its Analogues Reveals a Useful Biomarker for Fabry Disease - Sueoka, Hideaki; Ichihara, Junji; Tsukimura, Takahiro; Togawa, Tadayasu; Sakuraba, Hitoshi (PLOS ONE, 2015)
Biomarkers useful for diagnosis and evaluation of treatment for patients with Fabry disease are urgently needed. Recently, plasma globotriaosylsphingosine (lyso-Gb3) and lyso-Gb3-related analogues have attracted attention as promising biomarkers of Fabry disease. However, the plasma concentrations of lyso-Gb3 and its analogues are extremely low or below the detection limits in some Fabry patients as well as in healthy subjects. In this paper, we introduce the novel application of a nano-liquid chromatography-tandem mass spectrometry (nano-LC-MS/MS) system to the measurement of lyso-Gb3 and its analogues in plasma. Nano-LC-MS/MS requires smaller amounts of samples and is more sensitive than conventional techniques. Using this method, we measured the plasma concentrations of lyso-Gb3 and its analogues in 40 healthy subjects, 5 functional variants (males with E66Q), and various Fabry patients (9 classic Fabry males/9 mutations; 7 later-onset Fabry males/5 mutations; and 10 Fabry females/9 mutations). The results revealed that the mean lyso-Gb3 and lyso-Gb3(-2) concentrations in all the Fabry patient subgroups were statistically higher, especially in the classic Fabry males, than those in the functional variants and healthy subjects. The plasma concentrations of lyso-Gb3 and its analogues in healthy subjects, functional variants, and some Fabry patients with specific mutations (R112H and M296I) that cannot be established by conventional techniques were successfully determined by means of nano-LC-MS/MS. The lyso-Gb3 and lyso-Gb3(-2) concentrations in male patients with these mutations were lower than those in most Fabry patients having other mutations, but higher than those in the functional variants and healthy subjects. This new method is expected to be useful for sensitive determination of the plasma concentrations of lyso-Gb3 and its analogues. This study also revealed that not only lyso-Gb3 but also lyso-Gb3(-2) in plasma is a useful biomarker for the diagnosis of Fabry disease.